Sustained activation of the Aryl hydrocarbon Receptor transcription factor promotes resistance to BRAF-inhibitors in melanoma. Issue 1 (December 2018) - Corre, Sébastien; Tardif, Nina; Mouchet, Nicolas; Leclair, Héloïse; Boussemart, Lise; Gautron, Arthur; Bachelot, Laura; Perrot, Anthony; Soshilov, Anatoly; Rogiers, Aljosja; Rambow, Florian; Dumontet, Erwan; et al.
Abstract BRAF inhibitors target the BRAF-V600E/K mutated kinase, the driver mutation found in 50% of cutaneous melanoma. They give unprecedented anti-tumor responses but acquisition of resistance ultimately limits their clinical benefit. The master regulators driving the expression of resistance-genes remain poorly understood. Here, we demonstrate that the Aryl hydrocarbon Receptor (AhR) transcription factor is constitutively activated in a subset of melanoma cells, promoting the dedifferentiation of melanoma cells and the expression of BRAFi-resistance genes. Typically, under BRAFi pressure, death of BRAFi-sensitive cells leads to an enrichment of a small subpopulation of AhR-activated and BRAFi-persister cells, responsible for relapse. Also, differentiated and BRAFi-sensitive cells can be redirected towards an AhR-dependent resistant program using AhR agonists. We thus identify Resveratrol, a clinically compatible AhR-antagonist that abrogates deleterious AhR sustained-activation. Combined with BRAFi, Resveratrol reduces the number of BRAFi-resistant cells and delays tumor growth. We thus propose AhR-impairment as a strategy to overcome melanoma resistance. Resistance to BRAF inhibitors limits their clinical benefit in melanoma patients. Here, the authors show that the Aryl hydrocarbon Receptor (AhR) is a key mediator of resistant genes and use resveratrol, an AhR antagonist, to revert resistance in melanoma bearing mice.